2017
DOI: 10.1183/23120541.00047-2017
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1 deficiency reduces eosinophilia and interleukin-33 in an asthma exacerbation model

Abstract: Rhinovirus infections are common triggers of asthma exacerbations. Viruses can activate the inflammasome, resulting in processing and activation of caspase-1. This recruitment triggers production of interleukin (IL)-1β and IL-18, which have been implicated in asthma. Elucidating the involvement of the inflammasome and its compartments, such as caspase-1, in asthma exacerbations is warranted.Gene expression of caspase-1 was measured in rhinovirus-infected primary bronchial epithelial cells of asthmatic and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…The authors found that caspase-1 restrained expression of cleaved IL-33 and that up-regulation of airway inflammation in Casp1 −/− mice correlated with higher bioactive IL-33 expression and increased lung infiltration of eosinophils [ 191 ]. In contrast to this study, lack of caspase-1 reduced eosinophilia and mature bioactive lung IL-33 levels in an asthma exerbation model [ 192 ]. Another study showed that IL-33 treatment reduced NLRP3 inflammasome activation and IL-1β production in microglia and intracerebral monocytes in experimental cerebral malaria thereby ameliorating pathology in the brain [ 193 ].…”
Section: Nlrp3 Inflammasome and Il-33 In Sterile Inflammation-assocontrasting
confidence: 81%
“…The authors found that caspase-1 restrained expression of cleaved IL-33 and that up-regulation of airway inflammation in Casp1 −/− mice correlated with higher bioactive IL-33 expression and increased lung infiltration of eosinophils [ 191 ]. In contrast to this study, lack of caspase-1 reduced eosinophilia and mature bioactive lung IL-33 levels in an asthma exerbation model [ 192 ]. Another study showed that IL-33 treatment reduced NLRP3 inflammasome activation and IL-1β production in microglia and intracerebral monocytes in experimental cerebral malaria thereby ameliorating pathology in the brain [ 193 ].…”
Section: Nlrp3 Inflammasome and Il-33 In Sterile Inflammation-assocontrasting
confidence: 81%
“…Rhinoviral infection of PBECs is known to activate the NLRP3 and NLRC5 inflammasomes, leading to IL-1β release (26, 52). More recently, RV infection was found to increase caspase 1 expression to a greater extent in asthmatic PBECs than in normal cells, and in a house dust mite murine model of asthma exacerbations, caspase 1 knockout mice had reduced Th2 responses to poly(I:C) (53). Thus, a potential role of DUSP10 in regulating the inflammasome has significant implications for asthma.…”
Section: Discussionmentioning
confidence: 99%
“…However, LPS-induced lethality is reduced in IL-33-deficient mice [112] implying that IL-33 may contribute to the pyroptotic-generated inflammatory response. Nonetheless, in other inflammatory models, such as allergic asthma, caspase-1 has been reported to either limit [161], or increase [162], IL-33 levels.…”
Section: Il-33mentioning
confidence: 99%